2010
DOI: 10.1177/026119291003800613
|View full text |Cite
|
Sign up to set email alerts
|

Reporting the Implementation of the Three Rs in European Primate and Mouse Research Papers: Are We Making Progress?

Abstract: It is now more than 20 years since both Council of Europe Convention ETS123 and EU Directive 86/609?EEC were introduced, to promote the implementation of the Three Rs in animal experimentation and to provide guidance on animal housing and care. It might therefore be expected that reports of the implementation of the Three Rs in animal research papers would have increased during this period. In order to test this hypothesis, a literature survey of animal-based research was conducted. A randomly-selected sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 244 publications
2
15
0
Order By: Relevance
“…A small percentage of authors did mention efforts to minimize the number of animals and/or pain caused to animals in their studies. Our findings reflect a recent analysis of 250 research papers reporting experiments on primates and mice which found that reporting using the 3Rs is very low and not increasing (Taylor, 2011). Most often, authors referred to efforts to abide by a set of guidelines, such as those of the International Association for the Study of Pain (IASP, 2012), or approval by the researchers' institutional animal use committees.…”
Section: Discussionsupporting
confidence: 78%
“…A small percentage of authors did mention efforts to minimize the number of animals and/or pain caused to animals in their studies. Our findings reflect a recent analysis of 250 research papers reporting experiments on primates and mice which found that reporting using the 3Rs is very low and not increasing (Taylor, 2011). Most often, authors referred to efforts to abide by a set of guidelines, such as those of the International Association for the Study of Pain (IASP, 2012), or approval by the researchers' institutional animal use committees.…”
Section: Discussionsupporting
confidence: 78%
“…Some focus on animal welfare refinements and pain management, with little overt discussion of best practices for reliable, reproducible data. [ 1 , 5 13 ] Others have critiqued the animal research literature for concerns with transparency, data-quality and reproducibility, highlighting sources of bias that have also plagued human subjects research, such as randomization, robust statistics, and blinding of data-collectors to group allocations. [ 9 , 14 29 ] Recent guidelines for publishing animal studies, most notably from the UK National Centre for the 3Rs and the United States National Academies of Science, suggest standards for fuller and more consistent reporting of animal experimental methods in scientific articles, but with very little attention to animal pain management as a methodological practice of concern.…”
Section: Introductionmentioning
confidence: 99%
“…That may one day be true, but for now it is hampered by the lack of animal-welfare-relevant information in too many research articles. For example, a recent literature review indicated that in 2006, less than 5% of mouse research articles and 27% of primate research articles reported on the implementation (or justification for non-use) of painkillers [21]. These results suggest that the USDA's assertion may be of little value to researchers.…”
Section: Resultsmentioning
confidence: 99%